2015
DOI: 10.1016/j.renene.2015.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Importance of thermal dispersivity in designing groundwater heat pump (GWHP) system: Field and numerical study

Abstract: a b s t r a c tThrough field and numerical studies, this paper describes the importance of thermal dispersivity in designing groundwater heat pump (GWHP) systems. A pushepull test using heat as a tracer was performed to estimate the thermal dispersivity of the aquifer of this study at the Han River Environment Research Center in Korea. Measured data during the test were compared to the results of threedimensional (3-D) groundwater flow and heat transport simulations. From the best fit between the measured data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…On the other hand, as the plume also starts to expand in the unsaturated layers, the reduction of the thermal The drop of the plume length at high groundwater velocities can be explained by the fact that the separation of cold and hot plumes results in a more efficient heat exchange with the neighbouring layers (the vadose zone and aquitard), and, hence, the total length of the plume is reduced. Our results confirm the conclusion drawn in previous studies that the hydrodynamic parameters of the aquifer have a very strong influence on thermal plume size [44][45][46][47]. Hydraulic conductivity is the parameter most subject to uncertainties, depending on the method of determination [12,48]; therefore, it strongly affects the thermal impact quantification of GWHPs.…”
Section: Sensitivity Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, as the plume also starts to expand in the unsaturated layers, the reduction of the thermal The drop of the plume length at high groundwater velocities can be explained by the fact that the separation of cold and hot plumes results in a more efficient heat exchange with the neighbouring layers (the vadose zone and aquitard), and, hence, the total length of the plume is reduced. Our results confirm the conclusion drawn in previous studies that the hydrodynamic parameters of the aquifer have a very strong influence on thermal plume size [44][45][46][47]. Hydraulic conductivity is the parameter most subject to uncertainties, depending on the method of determination [12,48]; therefore, it strongly affects the thermal impact quantification of GWHPs.…”
Section: Sensitivity Analysissupporting
confidence: 90%
“…Figure 7d depicts the effect of such a mechanism on the longitudinal temperature distribution, comparing the assumptions of a no-flux boundary condition (second kind) applied to the ground surface and of the aforementioned reference temperature (third kind BC). The effect of heat exchange with neighbouring layers gets stronger over time (Figure 7b,d) and is negligible in the short term; this explains why previous studies, which considered short operating periods (less than one year [32,44,46]), concluded that heat conduction is negligible in GWHPs.…”
Section: Sensitivity Analysismentioning
confidence: 81%
“…The second layer, which represents the aquifer, is sub-divided into three sublayers. Simulations were performed under transient flow and transient transfer conditions using the forward Adams-Bashforth/backward trapezoidal predictor-corrector scheme for automatic time-step control [13]. The hydrogeological and thermal parameters of each layer used for the simulation are shown in Table 1.…”
Section: Geological Model Generalization and Discretizationmentioning
confidence: 99%
“…In recent years, scholars have conducted studies on GWHPs focusing on two aspects: reducing the environmental impact of groundwater pumping and improving the heat transfer efficiency of the GWHP system [13]. A commercial building in Rovigo, located in the Po River Plain (Italy), was chosen by Galgaro as a case study [14], and suggested that there are several heating/cooling timetables that reduce the risk of thermal feedback among wells and that these timetables may prevent the GWHP system from becoming uneconomical and energetically inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…With their model, they achieved a good agreement with reference numerical solutions. Park et al [7] studied Ground Water Heat Pump (GWHP) systems through a field test and numerical studies. The analysis confirmed that thermal dispersivity is a very important design factor when dealing with larger GWHP systems.…”
Section: Introductionmentioning
confidence: 99%